2014
DOI: 10.1111/cas.12438
|View full text |Cite
|
Sign up to set email alerts
|

Novel regulatory program for norepinephrine‐induced epithelial–mesenchymal transition in gastric adenocarcinoma cell lines

Abstract: Norepinephrine and epinephrine, catecholamine hormones that are major mediators for chronic stress-induced cancers, are implicated in the progression of a number of cancer cells, including gastric adenocarcinoma. However, the underlying mechanisms of these hormones have not been well elucidated. Epithelial–mesenchymal transition (EMT) is a crucial event responsible for cancer cell invasion and metastasis. The hypothesis regarding whether the promotive effects of norepinephrine (NE) on cancer are in part due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 29 publications
6
48
0
Order By: Relevance
“…In the present study, we demonstrated that stress activates the release of several substances different from catecholamines leading to an increase of migration of tumor cells from primary tumor to lymph nodes without affecting tumor growth (6). Additionally, we demonstrated that norepinephrine increased the expression of CK, MMP-2 and MMP-9 paralleled by EMT effects (E-cadherin loss and vimentin augmentation) (9)(10)(11)16), that are indispensable for metastasis formation. The combination of our results delivers good perspectives for the development of non-heart active and β2-specific blockers for the inhibition of metastasis development.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the present study, we demonstrated that stress activates the release of several substances different from catecholamines leading to an increase of migration of tumor cells from primary tumor to lymph nodes without affecting tumor growth (6). Additionally, we demonstrated that norepinephrine increased the expression of CK, MMP-2 and MMP-9 paralleled by EMT effects (E-cadherin loss and vimentin augmentation) (9)(10)(11)16), that are indispensable for metastasis formation. The combination of our results delivers good perspectives for the development of non-heart active and β2-specific blockers for the inhibition of metastasis development.…”
Section: Discussionsupporting
confidence: 49%
“…The differential remodeling of E-cadherin and vimentin has been characterized in cells that have undergone EMT. The loss of E-cadherin occurs in most epithelial cancers, and can be correlated to higher mobility and invasiveness of tumor cells (9,10). On the other hand, the increased vimentin expression is usually associated with increased in vitro motility of cancer cell lines (9,10).…”
Section: The Stress Hormone Norepinephrine Increases Migration Of Promentioning
confidence: 99%
“…It will be important to characterize if β 2 AR agonism induces similar behavior in other tumor cell lines and in vivo . Notably, several recent in vitro studies suggest that βAR signaling induces an epithelial-mesenchymal transition in gastric, colon and lung cancer cell lines (Lu et al, 2015; Shan et al, 2014; Zhang et al, 2016). To better understand βAR regulation of epithelial-mesenchymal transition it will be necessary to clarify the molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Shan et al showed that the human gastric cancer cell lines BGC-823 and SGC-7901 underwent morphological changes typical of EMT, and showed increased invasiveness, in response to co-culture with norepinephrine via a beta2-adrenergic signalling pathway [113]. Zhang et al showed a similar association between increased catecholamine signalling and initiation of EMT in HT-29 and A549 colorectal cancer cell lines [114].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%